Analisis Studi Kelayakan Bisnis Pada SK Computer Melalui Aspek Finansial dan Aspek Non Finansial - Nurlia Eka Damayanti; Dwi Sefriana; Eny Mariska; Priskila, Priskila; Veronika Trevesia G.; Yunita , Yunita (Ebisnis Manajemen, 2023)
This study aims to determine the business feasibility of Sk computer, through financial analysis aspects and non-financial analysis aspects. Where each aspect of this analysis becomes a basic assessment to determine feasibility in business. The analysis method used uses several analyzes from financial analysis aspects including financial aspects, market and marketing aspects, and non-financial aspects including human resources aspects, environmental aspects, cultural and economic aspects, and legal aspects. And the results of this research become an assessment to see the feasibility of the business and to become material to improve the Sk computer business.